ENDOPARASITES INFECTION IN BLOOD COCKLE (Anadara granosa) IN ACEH BESAR WATERS, INDONESIA - Putra, Dedi Fazriansyah; Ramadina, Suci; Mellisa, Siska; Abdullah Abbas, Muhammadar; He he, Xiao (Universitas Syiah Kuala, 2021)
This study aims to investigate the type, prevalence, and intensity of endoparasites infecting the organs of blood cockles (Anadara granosa) in the waters of Aceh Besar, Indonesia. A purposive sampling method was conducted from March to August 2020 consisting of two sampling sites, namely the waters of Ujung Pancu and Krueng Raya. Endoparasite identification and analysis was carried out at the Parasite Laboratory of the Fish Quarantine Center, Quality Control and Safety of Fishery Products in Blang Bintang, Aceh Besar. The results showed that there were two types of endoparasites living in the blood cockles: namely, Perkinsus sp., which belong to the group Protozoa, and Spiroxys sp. of the Nematode class. The prevalence levels of Perkinsus sp. was 73.33% and were found in the waters of Ujung Pancu; while the lowest prevalence level was 20% in blood cockles that were infected with Spiroxys sp., which were found both in Ujung Pancu and Krueng Raya. The highest intensity level was infections of Perkinsus sp. with a value of 89 ind/species in the Krueng Raya site. The lowest intensity value was infections of Spiroxys with a value of 2 ind/species in Krueng Raya and 2.3 ind/species in Ujung Pancu